2015
DOI: 10.1103/physrevd.92.065019
|View full text |Cite
|
Sign up to set email alerts
|

Flavor instabilities in the multiangle neutrino line model

Abstract: Neutrino flavor oscillations in the presence of ambient neutrinos is nonlinear in nature which leads to interesting phenomenology that has not been well understood. It was recently shown that, in the two-dimensional, two-beam neutrino Line model, the inhomogeneous neutrino oscillation modes on small distance scales can become unstable at larger neutrino densities than the homogeneous mode does. We develop a numerical code to solve neutrino oscillations in the multi-angle/beam Line model with a continuous neutr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 24 publications
(26 reference statements)
0
53
0
Order By: Relevance
“…We verified that the Fourier transform of P(t, z, u) has the same exponential growth rate as what is predicted by this analysis. Unlike stationary 2D models [34,35], however, there are no unstable spurious modes in this model. In Fig.…”
Section: Convective and Absolute Instabilitiesmentioning
confidence: 77%
“…We verified that the Fourier transform of P(t, z, u) has the same exponential growth rate as what is predicted by this analysis. Unlike stationary 2D models [34,35], however, there are no unstable spurious modes in this model. In Fig.…”
Section: Convective and Absolute Instabilitiesmentioning
confidence: 77%
“…Several recent studies, concerned primarily with anisotropic astrophysical environments, have demonstrated that the nonlinear neutrino self-coupling results in spatial instabilities [1][2][3][4]. These works indicate the importance of taking into account deviations from spherical symmetry in describing the evolution of, for example, the supernova neutrino flavor field.…”
Section: Introductionmentioning
confidence: 96%
“…In extreme environments with large neutrino number densities, such as the interior of a core-collapse supernovae (CCSN) and in the early universe, the nonlinearity associated with neutrino self-interactions lead to an array of interesting effects beyond the "standard" MSW [10,11]. These effects, which have their origin in the non-linear character of the neutrino evolution equations, include collective oscillations in an idealized model of supernova [12][13][14][15][16][17][18][19][20][21][22], matter-neutrino resonant behavior [23][24][25], spontaneous breaking of the axial symmetry [26,27], and Email addresses: cirigliano@lanl.gov (Vincenzo Cirigliano), mparis@lanl.gov (Mark W. Paris), shashank@lanl.gov (Shashank Shalgar) emergence of spatial inhomogeneity [1,2], to cite a few examples.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, they can result in flavor conversions close to the surface of the proto-neutron star (PNS) where it can be more influential. This is important since (if fast modes are absent) calculations have shown so far that significant neutrino flavor conversions are not likely to occur close to the surface of the PNS, in spite of the existence of flavor instabilities therein [38][39][40][41][42]. In fact, the unstable modes can turn stable before growing significantly due to the rapid variations of the physical conditions during the neutrino propagation [39,43].…”
Section: Introductionmentioning
confidence: 99%